Adjectives relate individuals to states: Evidence from the two readings of English Determiner + Adjective - Lelia Montague Glass (Glossa, 2019)
As an argument in favor of the (minority) view that adjectives involve a neo-Davidsonian state argument, I argue that it grounds an analysis of the English Determiner + Adjective construction (the old). On its “individuated” reading (the old are generally happier), this seems to refer to old individuals; on its “mass” reading (the old is never ordinary), to something like oldness. Empirically, this paper uses naturally-occurring data to show that both readings are more productive than sometimes  suggested. Theoretically, the two are parsimoniously derived by existentially closing off one or the other of the two arguments (the individual argument x, the state argument s) made available by the state analysis – λxλs[old(s) ∧ holder(x,s)] – deriving a predicate of individuals for the individuated reading, and a predicate of states for the mass reading. This account of Determiner + Adjective further reflects the philosophical idea that properties can be construed as predicates of individuals or as the abstract thing that those individuals share; and connects to other ways of nominalizing both verb phrases and adjectives.